Social Media, Economic Constraints, and Humanitarian Values: Drivers of Boycott Behavior Among Young Muslim Consumers in Indonesia - Faizi, Faizi; Putri, Indira Fadhilla; Bin Shuib, Mohd Sollehudin (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study investigates the influence of social media, economic factors, and humanitarian values on young Muslim consumers’ consumption preferences in Jabodetabek, Indonesia, regarding pro-Israel products amid ongoing boycott campaigns related to the Israel-Palestine conflict.Design/methodology: A quantitative approach was employed to collect data through surveys with 120 students in the Jabodetabek region. The Partial Least Squares (PLS) method was used for data analysis, focusing on variables such as social media exposure, price sensitivity, and ethical considerations.Findings: The results indicate that social media significantly shapes consumption preferences by disseminating information and forming public opinion, with platforms such as Instagram and TikTok playing a pivotal role. Economic factors, particularly price sensitivity and budget constraints, critically affect purchasing behavior, whereas humanitarian values, such as moral solidarity and ethical considerations, strongly motivate boycott participation. Collectively, these factors accounted for 62.8% of the variance in consumption preferences.Practical Implication: Businesses should adopt socially responsible branding and leverage social media to align themselves with consumer values. Policymakers and activists can use these insights to promote ethical consumption and support local alternatives.Originality/Value: This study integrates social media, economic, and humanitarian dimensions to offer a holistic understanding of boycott dynamics in an emerging economy. It bridges gaps in the literature by highlighting the interplay between digital influence, economic practicality, and moral convictions in consumer behavior